Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Ask your questions and receive precise answers from experienced professionals across different disciplines. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To determine the distance from point [tex]\(D\)[/tex] [tex]\((0, b)\)[/tex] to point [tex]\(A\)[/tex] [tex]\((0, 0)\)[/tex] in the coordinate plane, we can use the distance formula, which is given by:
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
For points [tex]\(A\)[/tex] [tex]\((0, 0)\)[/tex] and [tex]\(D\)[/tex] [tex]\((0, b)\)[/tex]:
- [tex]\(x_1 = 0\)[/tex], [tex]\(y_1 = 0\)[/tex]
- [tex]\(x_2 = 0\)[/tex], [tex]\(y_2 = b\)[/tex]
Plugging the coordinates into the distance formula:
[tex]\[ \text{Distance} = \sqrt{(0 - 0)^2 + (b - 0)^2} \][/tex]
Simplify the expression inside the square root:
[tex]\[ \text{Distance} = \sqrt{0 + b^2} \][/tex]
[tex]\[ \text{Distance} = \sqrt{b^2} \][/tex]
[tex]\[ \text{Distance} = b \][/tex]
Therefore, the correct formula to determine the distance from point [tex]\(D\)[/tex] to point [tex]\(A\)[/tex] is:
[tex]\[ \text{Distance} = \sqrt{(0-0)^2+(b-0)^2} = \sqrt{b^2} = b \][/tex]
Thus, the correct choice is:
D. [tex]\(\sqrt{(0-0)^2+(b-0)^2}=\sqrt{b^2}=b\)[/tex]
[tex]\[ \text{Distance} = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \][/tex]
For points [tex]\(A\)[/tex] [tex]\((0, 0)\)[/tex] and [tex]\(D\)[/tex] [tex]\((0, b)\)[/tex]:
- [tex]\(x_1 = 0\)[/tex], [tex]\(y_1 = 0\)[/tex]
- [tex]\(x_2 = 0\)[/tex], [tex]\(y_2 = b\)[/tex]
Plugging the coordinates into the distance formula:
[tex]\[ \text{Distance} = \sqrt{(0 - 0)^2 + (b - 0)^2} \][/tex]
Simplify the expression inside the square root:
[tex]\[ \text{Distance} = \sqrt{0 + b^2} \][/tex]
[tex]\[ \text{Distance} = \sqrt{b^2} \][/tex]
[tex]\[ \text{Distance} = b \][/tex]
Therefore, the correct formula to determine the distance from point [tex]\(D\)[/tex] to point [tex]\(A\)[/tex] is:
[tex]\[ \text{Distance} = \sqrt{(0-0)^2+(b-0)^2} = \sqrt{b^2} = b \][/tex]
Thus, the correct choice is:
D. [tex]\(\sqrt{(0-0)^2+(b-0)^2}=\sqrt{b^2}=b\)[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.